Changes in corneal sensitivity following cross-linking for progressive early-stage keratoconus - Lago,Anelise de Medeiros (2014)
Purpose: To evaluate changes in corneal sensitivity following corneal cross-linking (CXL) in patients with progressive earlier stage keratoconus. Methods: Thirty-eight eyes of 19 patients (11 women, 8 men) were included in a prospective, nonrandomized clinical study. The mean patient age was 22 years (range, 18-26 years). Inclusion criteria were early stage bilateral progressive keratoconus, a transparent cornea, and a thickness of ≥440 µm in the thinnest area of the cornea. Using the Cochet-Bonnet esthesiometer, central corneal sensitivity was measured before surgery, 7 days after surgery, and once a month thereafter until recovery of baseline preoperative levels. Central corneal sensitivity >40 mm was considered normal. Results: Corneal sensitivity gradually returned to preoperative levels in all treated eyes. The mean central corneal sensitivity was 52.2, 24.0, 38.2, 42.5, 50.0, and 52.5 mm before surgery, 7 days after surgery, and at 1, 2, 3, and 4 months after surgery, respectively. Normal levels of corneal sensation, but not baseline (preoperative) levels, were observed 2 months after surgery. The preoperative levels were observed 3 months after surgery. Conclusions: Our results suggest that central corneal sensitivity can be decreased for as long as 3 months after CXL for progressive earlier stage keratoconus.